Principles of computer organization and assembly language : using the Java virtual machine - Juola, Patrick (Upper Saddle River, New Jersey : Pearson/Prentice Hall, 2007)
This innovative book introduces the principles of computer organization and assembly language through the example of the Java Virtual Machine: a platform that is exceptionally convenient, modern, portable, and nearly universally available. Using the JVM implementation as a foundation, Patrick Juola gives an accessible and easy to understand explanation of digital logic and systems, data representation, machine organization, architecture, and the fundamentals of assembly language programming. Once readers thoroughly understand these core principles in the context of the JVM, Juola extends them to four other leading platforms: the Intel 8088, Pentium 4, Power architecture, and the Atmel AVR microcontroller.
1. Computation and representation -- 2. Arithmetic expressions -- 3. Assembly language programming in jasmin -- Control structures -- General architecture issues : real computers -- The Intel 8088 -- The power architecture -- The Intel pentium -- Microcontrollers : the Atmel AVR -- Advanced programming topics on the JVM.
Includes bibliographical references and index.
Keywords: JAVA VIRTUAL MACHINE